Wall effect on settling of cylindrical particles - Wong, Wen Yin. (2009)
Settling of solid cylindrical particles in fluid medium is important in many chemical processes such as settlers. The relative velocity between fluid and cylinder affect heat and mass transfer between them. However, the settling of cylinder is not extensively studied compared to spherical particle. The cylindrical particles are made of stainless steel and aluminum which diameter varies from 2mm to 14 mm and length from 8 to 64mm are used in the experiment. The particles are drop from rest into column filled with water. The retardation due to wall effect is quantified in terms of wall factor. This project investigates the movement of particle and relationship between wall factor, particle size, density, column diameter and dimension at two turning points namely critical point 1 and 2. The Reynolds number falls in the Newton regime ranging from 1000 to 20000. Expressions relating wall factor and column diameter to particle size, dimension are presented and it correlates well with the data obtained.